State-of-the-art catalysts for clean fuel (methyl esters) production—a comprehensive review - Farrukh Jamil; Muhammad Saleem; Obaid Ali Qamar; M Shahzad Khurram; Ala’a H Al-Muhtaseb; Abrar Inayat; Parveen Akhter; Murid Hussain; Sikander Rafiq; Hyunji Yim; Young-Kwon Park (JPhys Energy, 2022)
There has been growing and recent interest in using non-edible feedstocks, such as waste animal fats, as an alternative to vegetable oils in biodiesel production to address the food versus fuel debate. Waste animal fats are cost effective and yield good quality biodiesel. Therefore, waste animal fats are appealing and excellent feedstocks to produce biodiesel. Commercially, the biodiesel is obtained by transesterification reaction of triglycerides present in oil/fat with alcohol in the presence of homogeneous base catalysts. However, free fatty acids found in low-quality oil feedstocks are particularly sensitive to homogeneous base catalysts, necessitating extra acid pretreatment and neutralization procedures that not only raise the overall expense of producing biodiesel but also create environmental contamination. Optimistically, the use of solid catalysts can offer an environmentally friendly, cost-effective and practical route for the manufacture of biodiesel from inexpensive oil feedstocks, including waste animal fat. The present review article covers catalyzed transesterification/esterification using various catalysts with particular focus on the use of heterogeneous catalysts when using waste animal fat as feedstock for biodiesel production. In particular, the properties of biodiesel obtained from waste animal fats are also compared to the biodiesel properties of standard organizations, such as the European Committee for Standardization (ISO) and the American Society for Testing and Materials (ASTM). Moreover, this paper also offers future research directions that can direct researchers to fill in knowledge gaps impeding the creation of efficient heterogeneous catalysts for long-term biodiesel generation. To the best of our knowledge, the valorization of waste animal fats from slaughterhouses is not feasible and has some techno-economic concerns. However, this technology is more desirable considering the environmental point of view to address the pollution problems caused by these wastes.